Compensation Method for Temperature Cross-Sensitivity in Transverse Force Applications with FBG Sensors in POFs - Leal-Junior, Arnaldo G.; Theodosiou, Antreas; Marques, Carlos; Pontes, Maria José; Kalli, Kyriacos; Frizera, Anselmo (My University, 2018)
In this paper, we investigate the influence of temperature on the transverse force response of polymer optical fiber Bragg gratings (POFBGs) inscribed in cyclic transparent fluoropolymers (CYTOPs). The gratings are imprinted in the fiber using the direct-write, plane-by-plane femtosecond laser inscription method. The temperature increase leads to a decrease in the polymer Young's modulus, which causes a sensitivity variation in the POFBG sensor for transverse force applications. The proposed technique is based on the characterization of both the sensor's response offset and the material's Young's modulus variation due to the temperature increase. Transverse force tests were performed at different temperatures (30 °C, 40 °C, 50 °C, and 60 °C) and the compensated and uncompensated responses are compared in terms of root mean squared error (RMSE). The compensated results show an RMSE lower than 3% (mean value between all tested temperatures), which is 6.7 times lower compared with the uncompensated response. In addition, the proposed compensation technique presents a maximum RMSE reduction of 16 times at 60 °C.
Keywords: Fiber Bragg gratings; Polymer optical fiber; Temperature; Transverse force